Proteostasis of α-Synuclein and Its Role in the Pathogenesis of Parkinson’s Disease - Han, Deqiang; Zheng, Wei; Wang, Xueyao; Chen, Zhiguo (Frontiers in Cellular Neuroscience, 2020)
Aggregation of α-Synuclein, possibly caused by disturbance of proteostasis, has been identified as a common pathological feature of Parkinson’s disease (PD). However, the initiating events of aggregation have not been fully illustrated, and this knowledge may be critical to understanding the disease mechanisms of PD. Proteostasis is essential in maintaining normal cellular metabolic functions, which regulate the synthesis, folding, trafficking, and degradation of proteins. Toxicity of the aggregating proteins is dramatically influenced by its physical and physiological status. Genetic mutations may also affect the metastable phase transition of proteins. In addition, neuroinflammation as well as lipid metabolism and its interaction with α-Synuclein are likely to contribute to pathogenesis of PD. In this review, we will highlight recent progress regarding α-Synuclein proteostasis in the context of PD. We will also discuss how phase transition status of α-Synuclein could correlate with different functional consequences in PD.